Development of Scientific Learning Model on Trading Company Accounting Subject for XI Class students of Accounting Department of SMK Negeri 1 Malang - Rahmadany, Mirza (Unversitas Negeri Malang, 2017)
The purpose of this research is to develop Problem Based Learning and Project Based Learning using scientific learning approach in accounting subjects of class XI trading companies Accounting of SMK Negeri 1 Malang. This type of research is the development of research using a development model Borg and Gall (1983) which has been modified according to the needs of research. The trial subject of this research is the subject teachers as well as the trading company's accounting class XI AK 3 and 4 which respectively accounted for 36 and 31 students. Data were analyzed using content analysis techniques and descriptive percentage. The results validate learning experts obtained a value of 84.38%, 75% of subject matter experts, 77.26% of the experts the development of teaching materials, as well as from the user namely 75% of teachers and students by 82.29%. The average percentage of 79.79% for the overall learning model, 75% for instructional material contained in the book of teachers and students, as well as 77.26% of the student book so it can be concluded that the learning model that consists of teachers and students developed books is feasible and can be used in the learning process.Â Keywords: scientific learning model, accounting, project-based learningÂ DOI:Â 10.17977/um013v1i22017p082